Development of Interactive Student’s Worksheets to Improve Mathematical HOTS of Tenth Grade Students in Trigonometry Topic - Bertha Oktavika Sembiring; E Elvis Napitupulu (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2022)
It is undeniable that Higher Oder Thinking Skills (HOTS) have become the center of attention and essential skills needed, especially in mathematics today, but there are so many research shows that the average thinking ability of Indonesian students is still low. One of the student's low thinking abilities cause is teaching materials that still dominated by questions in the Low Order Thinking Skills (LOTS) category. Therefore, this study aims to develop valid, practical, and effective interactive student worksheets to improve tenth-grade students' higher-order thinking skills. This research used Research and Development (R&D) designs and methods guided by the ADDIE development model with five steps: Analysis, Design, Development, Implementation, and Evaluation. The data obtained from this study is quantitative and qualitative data, which was obtained from the interview, validation test sheet, students and teacher response sheet and pretest-posttest result. The assessment from experts from both the material and media shows that the worksheet is valid with 4.30 and 3.97 average scores. Furthermore, based on the questionnaire responses of teachers and students with the